Lymphotoxin α fine-tunes T cell clonal deletion by regulating thymic entry of antigen-presenting cells - Noëlla Lopes (Nature Portfolio, 2018)
Autoreactive T cells are removed during their development in the thymus through the functions of medullary thymic epithelial cells (mTEC) and dendritic cells (DC), a process termed negative selection. Here the authors show that mTEC-T cell crosstalk and lymphotoxin α signalling are essential for the proper recruitment of DCs into the thymus.